Progesterone alleviates neural behavioral deficits and demyelination with reduced degeneration of oligodendroglial cells in cuprizone-induced mice. - Jian-Ning Ye (Public Library of Science (PLoS), 2013)
Demyelination occurs widely in neurodegenerative diseases. Progesterone has neuroprotective effects, is known to reduce the clinical scores and the inflammatory response. Progesterone also promotes remyelination in experimental autoimmune encephalomyelitis and cuprizone-induced demyelinating brain. However, it still remains unclear whether progesterone can alleviate neural behavioral deficits and demyelination with degeneration of oligodendroglial cells in cuprizone-induced mice. In this study, mice were fed with 0.2% cuprizone to induce demyelination, and treated with progesterone to test its potential protective effect on neural behavioral deficits, demyelination and degeneration of oligodendroglial cells. Our results showed noticeable alleviation of neural behavioral deficits following progesterone treatment as assessed by changes in average body weight, and activity during the open field and Rota-rod tests when compared with the vehicle treated cuprizone group. Progesterone treatment alleviated demyelination as shown by Luxol fast blue staining, MBP immunohistochemical staining, and electron microscopy. There was an obvious decrease in TUNEL and Caspase-3-positive apoptotic cells, and an increase in the number of oligodendroglial cells staining positive for PDGFRα, Olig2, Sox10 and CC-1 antibody in the brains of cuprizone-induced mice after progesterone administration. These results indicate that progesterone can alleviate neural behavioral deficits and demyelination against oligodendroglial cell degeneration in cuprizone-induced mice.